If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19m + 42 = 0 Reorder the terms: 42 + 19m = 0 Solving 42 + 19m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 19m = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 19m = 0 + -42 19m = 0 + -42 Combine like terms: 0 + -42 = -42 19m = -42 Divide each side by '19'. m = -2.210526316 Simplifying m = -2.210526316
| 100x-x=14 | | 7f+5=5f+17 | | 41x=14 | | I=(89)(.075)(.5) | | 4x-6x+2x-8x= | | 3x+(2x+10)=5 | | 18s=10 | | (8x+22)=(5x+15) | | 0.4*x=X-100 | | 18+6.50(x-3)= | | 725.4656=4*3.14*r^2 | | 4392.1064=4*3.14*r^2 | | y=17sin(8t) | | a^2+7ab-18n^2=0 | | 8x-37=4x+27 | | -5k-4(k-3)=-6k+3 | | 5(x+2)-3=2x+3(1+x) | | 40*x=X-100 | | 6m^2+2m-17=0 | | (2x+6)+(x+9)=90 | | 2x-3y(x-1)=-1 | | -k+35=-7(-5-8k) | | 107+2x-5=180 | | 2(2+3y)+3y=15 | | x+2x-5=107 | | 9x^2-70+49=0 | | 2x+-3y(6x-11)=-7 | | (6x^2)-30x=0 | | (6x^2)-30y=0 | | (6x+48)=(12x+24) | | 26.2=9t | | 3b-3-4b=2 |